Validating the LDi and LCi Indices in the Southern Hemisphere - E. Nahayo; A. Guerrero; S. Lotz; C. Cid; M. Tshisaphungo; E. Saiz (Space Weather)
Abstract The validation of the Local Disturbance index (LDi) and its first time derivative Local Current index (LCi) is performed in the Southern Hemisphere. Two South African magnetic observatories, Hermanus and Hartebeesthoek contributed data for this study, and two South African power stations, Grassridge and Matimba, provided geomagnetically induced current (GIC) data. This validation focused on two major geomagnetic storms, Halloween and Saint Patrick's Day events that occurred in October 2003 and March 2015, respectively. The comparative evaluation of the LDi and LCi indices was executed with the help of the local horizontal component (H) and also comparing them to the global index SYM‐H. A direct comparison to measured GIC shows that LCi performs slightly better than dH/dt as a proxy for GIC. The comparison of the LDi 1‐hr magnetic disturbances values to ones calculated applying a Linear phase Robust Non‐Smoothing method to the H component yields a Pearson correlation coefficient R greater than 0.960 for different groups of magnetic storms based on intensity. The estimated SYM‐H index from LDi data showed a possible difference of about 300 nT from the published SYM‐H index values around 20:00 UT on 29 October 2003, during the Halloween storm. This study has shown that the LDi and LCi indices, developed in the Northern Hemisphere, can be calculated at similar latitudes in the Southern Hemisphere for studying local space weather conditions and now‐casting successfully local geomagnetic events.